RANCANG BANGUN RANGKA PADA MESIN PENGIRIS BAWANG MERAH DAN BAWANG BOMBAY TENAGA HIBRID - Sunarya, Aldan; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2024)
With the development of technology, especially in MSMEs and the demand to create a tool that has the ability to reduce the risk of injury when slicing onions and streamline the slicing process time. The shallot and onion slicing machine hybrid power is a tool that functions to slice onions in a short time. This machine is a tool that is driven by motor power and has been designed in one machine construction with adjusted dimensions so as to increase safety and time efficiency. The design of the shallot and onion slicing machine frame hybrid power with the following specifications: machine dimensions 520mm x 300mm x 300mm with 220V motor power is intended to be able to overcome the problem of shallot and onion production. The frame is an important element that cannot be separated in the design and manufacture of a machine. The frame functions as a support or foundation for the components of the machine. The material used to make the frame of the onion and onion slicing machine is angle iron with dimensions of 40 x 40 x 3 mm and the type of material used is low carbon steel. In designing and manufacturing the frame for the shallot and onion slicing machine, the material used is ST37 specification steel with a maximum tensile or compressive stress of 370 N/  and a permissible stress of 240 N/.